Caiman Versus LigaSure Hemorrhoidectomy: Postoperative Pain, Early Complications, Long-Term Follow-up, and Costs. (June 2020) - Eberspacher, Chiara; Mascagni, Pietro; Di Nardo, Domenico; Pironi, Daniele; Pontone, Stefano; Martellucci, Jacopo; Naldini, Gabriele; Mascagni, Domenico
Purpose. Recently, the use of radiofrequency for hemorrhoidectomy has minimized incidence of postoperative complications. Effectiveness of LigaSure is demonstrated, but it is quite expensive. This study aims to compare LigaSure with Caiman, a cheaper instrument that uses radiofrequency for hemorrhoidectomy. Methods. A total of 35 patients were enrolled in this study between January 2015 and December 2017: 35 (Group A: Caiman) patients were matched with 35 control patients (Group B) from our historical cohort, treated with LigaSure. They were checked at 1 week after operation, at 4 weeks, and then after 2, 6, and 12 months. We considered different factors: intraoperative (operative time, number of piles removed, necessity of stiches or ligation), immediate postoperative (pain, bleeding within 4 weeks, incontinence, soiling within 4 weeks, healing time of anal wounds, return to working activities), and with a long-term follow-up. Results. There were no statistically significant differences between the 2 groups in analyzed intraoperative data: operative time (Group A 35 minutes vs Group B 33 minutes; P = .198) and stitches used. Postoperative data were comparable too, in particular pain (Group A 1 day Visual Analog Score = 6.25 vs Group B = 5.4, P = .178; Group A 1 week Visual Analog Score = 2.7 vs Group B = 1.14, P = .22) and bleeding (Group A = 2 vs Group B = 4; P = .2). Conclusions. According our initial experience, Caiman can be a safe and cheaper alternative to LigaSure for hemorrhoidectomy.